The eacher's Efforts to Improve Early Childhood Science Ability Through the Application of Experimental Methods to Recognize Colors Using Flower Plants - Dina, W S; Masterjon, Masterjon; Partikasari, R; Yulmiarti, Yulmiarti (Early Childhood Research and Practice, 2023)
The purpose of this study was to determine the early childhood scientific ability through the application of the experimental method to recognize color using flower plants, to determine the increase in early childhood scientific ability through the application of the experimental method to recognize color using flower plants. Classroom Action Research (PTK) which is focused on class situations, or known as classroom action procedures used in the form of cycles. The main subjects in the study were 15 children in the AL-MUTTAQIN PAUD in Talang Dantuk Village, Seluma District, Seluma Regency. Data collection techniques using observation and documentation methods. Data analysis was carried out in a qualitative descriptive manner by using it to determine the process improvement expressed in a predicate, while quantitative data analysis was used to determine the increase in results by using a percentage. The conclusion of this study is that children's initial scientific abilities through the experimental method of knowing colors using flower plants develop well